SOCY 362: Contemporary Social Theory - Kohlman, Marla H. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In this core course we will investigate the twentieth century’s major theories concerning the nature of society and the human social process. Most of these sociological theories are American in origin, but some developments in Western European thought will also be included. Specific theories to be discussed include functionalism, symbolic interactionism, conflict, critical theory, and intersection theory. The consideration of the intellectual and social contexts in which these theoretical traditions have arisen will be central to our analysis throughout. This course will be of value to students interested in developing a systematic approach to understanding society and should be especially relevant to those concentrating in the social sciences.